Rosai-Dorfman Disease (Sinus Histiocytosis with Massive Lymphadenopathy): A Case Report - Hamdi Çaklı; Sevilay Küçük; Emre Cingi; Erkan Özüdoğru; K›smet Bildirici (Turkish Archives of Otorhinolaryngology, 2003)

(untitled)
Rosai-Dorfman disease is a rare benign idiopatic histiocytic proliferative disorder. It is also known as sinus histiocytosis with massive lymphadenopathy. The disease is characterized by painless cervical lymphadenopathy, variably associated with fever, elevated erythrocyte sedimentation rate, weight loss, polyclonal hypergammaglobulinaemia, involvement of extra nodal organs such as brain, breast, skin, orbit ear, and gastrointestinal tract, upper respiratory tract, spine. The cause of this disease is still unknown. The precise diagnosis is performed by lymph node biopsy. Various treatment modalities include surgery, chemotherapy, antibiotics, steroids, radiotherapy or the combination of these have been tried, but convenient therapy model hasn’t been emerged. Most of them have been reported to regress spontaneously. Death is a very rare complication and reported due to infiltration of vital organs. In this report the findings of a 52 years old woman who was admitted to our clinic with painless cervical lymphadenopathy is presented, the findings and the treatment is compared with the literature.